2016
DOI: 10.1214/16-ba1017
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Solution Uncertainty Quantification for Differential Equations

Abstract: We explore probability modelling of discretization uncertainty for system states defined implicitly by ordinary or partial differential equations. Accounting for this uncertainty can avoid posterior under-coverage when likelihoods are constructed from a coarsely discretized approximation to system equations. A formalism is proposed for inferring a fixed but a priori unknown model trajectory through Bayesian updating of a prior process conditional on model information. A one-step-ahead sampling scheme for inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
190
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(191 citation statements)
references
References 39 publications
1
190
0
Order By: Relevance
“…A recent Probabilistic Numerics methodology for ODEs (Chkrebtii et al 2013) [explored in parallel in Hennig and Hauberg (2014)] has two important shortcomings. First, it is impractical, only supporting first-order accurate schemes with a rapidly growing computational cost caused by the growing difference stencil [although Schober et al (2014) extends to Runge-Kutta methods].…”
Section: Review Of Existing Workmentioning
confidence: 99%
“…A recent Probabilistic Numerics methodology for ODEs (Chkrebtii et al 2013) [explored in parallel in Hennig and Hauberg (2014)] has two important shortcomings. First, it is impractical, only supporting first-order accurate schemes with a rapidly growing computational cost caused by the growing difference stencil [although Schober et al (2014) extends to Runge-Kutta methods].…”
Section: Review Of Existing Workmentioning
confidence: 99%
“…For algebraic as well as conceptual reasons [4], GPs are a preferable choice for the prior distribution. We first review GPs and then discuss their application in ODE solvers.…”
Section: Probabilistic Ode Solversmentioning
confidence: 99%
“…Therefore, as discussed in Dass (2016), the fact that C N → 0 alone is not enough to ensure convergence. In the Supplement (Chkrebtii et al, 2016b) we have shown that the posterior expectation …”
Section: Rate Of Convergencementioning
confidence: 90%
“…Our rejoinder is divided into six sections, which provide insight and clarification on the subjects that were raised by the discussants. The paper by Chkrebtii et al (2016a) and the proposed formalism will hereafter be referred to as UQDE (uncertainty quantification for differential equations).…”
Section: Introductionmentioning
confidence: 99%